2011
DOI: 10.1371/journal.ppat.1002070
|View full text |Cite
|
Sign up to set email alerts
|

MDA5 and TLR3 Initiate Pro-Inflammatory Signaling Pathways Leading to Rhinovirus-Induced Airways Inflammation and Hyperresponsiveness

Abstract: Rhinovirus (RV), a single-stranded RNA picornavirus, is the most frequent cause of asthma exacerbations. We previously demonstrated in human bronchial epithelial cells that melanoma differentiation-associated gene (MDA)-5 and the adaptor protein for Toll-like receptor (TLR)-3 are each required for maximal RV1B-induced interferon (IFN) responses. However, in vivo, the overall airway response to viral infection likely represents a coordinated response integrating both antiviral and pro-inflammatory pathways. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
124
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(134 citation statements)
references
References 47 publications
(60 reference statements)
8
124
2
Order By: Relevance
“…We also found significant overexpression of the IFIH1 gene encoding MDA-5, an intracellular RNA helicase that recognizes viral doublestranded RNA. We have shown that, in contrast to RIG-I, MDA-5 expression is increased on RV infection in airway epithelial cells and is required for maximal RV-induced cytokine and IFN production in both human airway epithelial cells (43) and mouse lungs (44). Together, these data demonstrate that patients with CF with RV-associated respiratory exacerbations generate an antiviral response similar in character to that observed in experimental systems.…”
Section: Discussionsupporting
confidence: 55%
“…We also found significant overexpression of the IFIH1 gene encoding MDA-5, an intracellular RNA helicase that recognizes viral doublestranded RNA. We have shown that, in contrast to RIG-I, MDA-5 expression is increased on RV infection in airway epithelial cells and is required for maximal RV-induced cytokine and IFN production in both human airway epithelial cells (43) and mouse lungs (44). Together, these data demonstrate that patients with CF with RV-associated respiratory exacerbations generate an antiviral response similar in character to that observed in experimental systems.…”
Section: Discussionsupporting
confidence: 55%
“…2010; Wang et al. 2011, 2009). While there is some controversy over whether or not NF‐ κ B p65 is required for RV‐induced IFN transcription (Bartlett et al.…”
Section: Discussionmentioning
confidence: 99%
“…TLR3 activation induces production of allergen-specific IgE and IgG1 (38). TLR3 null mice shows decreased rhinovirus-induced airway inflammatory and contractile responses (39). Poly(I:C) (TLR3) stimulation increases the secretion of IL-6 and GM-CSF from the nasal mucosa and the epithelial cell lines (40).…”
Section: Discussionmentioning
confidence: 99%